In vitro assessment of dentin erosion after immersion in acidic beverages: Surface profile analysis and energy-dispersive X-ray fluorescence spectrometry study - Caneppele, Taciana Marco Ferraz [UNESP]; Jeronymo, Raffaela Di Iorio [UNESP]; Di Nicoló, Rebeca [UNESP]; de Araújo, Maria Amélia Máximo [UNESP]; Soares, Luís Eduardo Silva (FapUNIFESP (SciELO), 2012)
The aim of this study was to investigate the effects of some acidic drinks on dentin erosion, using methods of surface profile (SP) analysis and energy-dispersive X-ray fluorescence spectrometry (EDXRF). One hundred standardized dentin slabs obtained from bovine incisor roots were used. Dentin slabs measuring 5x5 mm were ground flat, polished and half of each specimen surface was protected with nail polish. For 60 min, the dentin surfaces were immersed in 50 mL of 5 different drinks (Gatorade®, Del Valle Mais orange juice®, Coca-Cola®, Red Bull® and white wine), 20 blocks in each drink. The pH of each beverage was measured. After the erosive challenge, the nail polish was removed and SP was analyzed. The mineral concentration of dentin surfaces was determined by means of EDXRF. Data were analyzed statistically by ANOVA and Tukey's test (α=0.05). SP analysis showed that Red-Bull had the highest erosive potential (p<0.05). EDXRF results exhibited a decrease in phosphate in the groups immersed in Red-Bull, orange juice and white wine (p<0.05), and no significant difference in calcium content between the reference surface and eroded surface. In conclusion, this study demonstrated that all studied beverages promoted erosion on root dentin and Red Bull had the highest erosive potential. There was no correlation between pH of beverages and their erosive potential and only the P content changed after erosive challenge.
Keywords: Beverages; Dental erosion; pH; X-ray fluorescence spectrometry